2010
DOI: 10.1259/dmfr/23992216
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ultrasound patterns of parotid glands in human immunodeficiency virus-positive patients in Mulago, Uganda

Abstract: Objectives: The purpose of this study was to determine sonographically, in parotid glands of human immunodeficiency virus-positive patients, the condition of glands with or without enlargement, and propose a classification system for the patterns observed using diagnostic ultrasound imaging. Methods: In this prospective clinical study, ultrasound scans were performed on 200 patients aged 4-62 years at Mulago Hospital, Uganda. Results: There were four main distinct ultrasound pathological patterns in the paroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The US examination of the parotid glands showed that 67.65% of children with a history of parotid gland enlargement and 50% of children with no history showed changes in the parotid glands consistent with the diagnosis of HIV/SGD, corroborating the results of Goddart et al . and Kabenge et al …”
Section: Discussionsupporting
confidence: 84%
“…The US examination of the parotid glands showed that 67.65% of children with a history of parotid gland enlargement and 50% of children with no history showed changes in the parotid glands consistent with the diagnosis of HIV/SGD, corroborating the results of Goddart et al . and Kabenge et al …”
Section: Discussionsupporting
confidence: 84%
“…3,11 The cysts are painless, slow-growing, 11 frequently bilateral, 4,11 soft in consistency and involve the superficial lobe of the parotid gland, 4 with multiple cysts being more common than single. 12 Their size varies from 0.5 cm to 5 cm in diameter.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…3 Computed tomography and magnetic resonance imaging. Multiple small cysts with enlarged parotid glands are usually observable on CT and MRI scans.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover the parenchyma of salivary glands are subjected to other influences such as hormones that affect changes in its morphological characteristics leading to local or systemic alterations. 1 One such change is adipose tissue infiltration between acini parenchyma associated with conditions like: Human Imunodeficiency virus (HIV), 2 hypertriglyceridemia, 3 but most commonly with ageing in the absence of any obvious disease process 4,5 .…”
Section: Introductionmentioning
confidence: 99%